The Role of Academic Hardiness in Moderating the Effect of Task Aversiveness on Academic Procrastination - Tahrir, Tahrir; Arifah, Fathimah N.; Augustiya, Tasya; Nasrudin, Endin (Psympathic : Jurnal Ilmiah Psikologi, 2024)
This research aimed to examine the role of academic hardiness as a moderator in the effect of task aversiveness on academic procrastination using quantitative causal and proportional stratified random sampling methods. The sample consisted of 260 psychology students from Sunan Gunung Djati State Islamic University (UIN), Bandung. The data were collected through questionnaires using Task Aversiveness, Academic Procrastination, and Revised Academic Hardiness Scale (RAHS). Additionally, data analysis was performed using simple regression tests and Moderated Regression Analysis (MRA). The results showed that task aversiveness and academic hardiness significantly increased and decreased academic procrastination, respectively. In conclusion, academic hardiness did not moderate the effect of task aversiveness on procrastination.